GAMBARAN PENGETAHUAN KESEHATAN GIGI DAN MULUT MELALUI MEDIA GAMBAR PADA SISWA SISWI DI SD PERTIWI MAKASSAR - Feblina, Ayu Rahayu; Alimuddin, Hadijah; Pariati, Pariati; Alfah, Siti; Rahmadani, Nanang (Jurnal Ilmiah Amanah Akademika, 2021)
Image media is one of the media used as a support to improve student learning outcomes. Media images provide a very good influence in improving student learning outcomes. This is because the use of media images in the learning process can attract the attention of students so that students are more serious in defending the teacher's explanation. This type of research is descriptive. This research was carried out on an observational basis with the aim of knowing the description of children's knowledge about oral health through the medi of images in grade 1 and 2 students at SD Pertiwi Makassar . The number of samples in this study were 43 students. Primary data obtained through filling out questionnaires by respondents. The results of the research on the description of children's knowledge about dental and oral health through the media of pictures in grade 1 and 2 students at SD Pertiwi Makassar , totaling 43 children. There are results of majority knowledge in the good category (93.02%), sufficient knowledge (6.98%). Through drawing dental and oral health, children will receive education about dental and oral health through learning drawing activities so that it can affect their knowledge. So it is expected that parents can apply information to children about foods that are healthy for teeth, foods that are not healthy for teeth, how to brush teeth, and control to the dentist in everyday life.